10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Substance Use Disorder (SUD) treatment in sub-Saharan Africa remains poorly understood from the perspectives of those who deliver and receive it. We integrated the perspectives of service users (SUs) and front-line health care workers (HCWs) within a single analytic frame to map SUD treatment trajectories and identify multilevel barriers and facilitators shaping treatment and recovery outcomes in Uganda. We conducted a qualitative study nested within a parent cohort of adults treated for SUDs at two public treatment facilities in Uganda. We conducted in-depth interviews with 43 SUs from this cohort and 10 HCWs directly involved in SUD care. We analysed the data using reflexive thematic analysis. SU and HCW data accounts were first analysed separately before applying integrative mapping to generate cross-cutting meta-themes. We identified four interrelated meta-themes. First, systemic and structural constraints, including human resource gaps, medication stockouts, and inadequate infrastructure, undermined care consistency and quality. Second, accounts suggested that SUD care was only partially aligned with the biopsychosocial model, with acute biomedical stabilisation more consistently implemented than psychosocial support, individualised care, and recovery planning. Third, participants described returning to high-risk post-treatment environments marked by stigma, weak family support, peer and environmental triggers, economic insecurity, and untreated comorbidities, which increased perceived relapse vulnerability. Fourth, they identified supportive anchors for recovery, including faith and spirituality, active coping, family and community engagement, peer mentorship, task-sharing, and strengthened multidisciplinary care. Participants' accounts indicate that SUD care and recovery in Uganda are shaped by a self-reinforcing cycle of system constraints, fragmented care, and high-risk post-discharge environments. Reorienting SUD care towards a recovery-oriented continuum will require stronger links between facility-based treatment and community support, alongside investment in psychosocial care, workforce capacity, service infrastructure, and locally available recovery resources.